Evaluation of reference signal estimation techniques for the control of shunt active power filter - Atan N.B.; Yunus B.B. (2023)
This paper presents the implementations of a new control algorithm for a three-phase shunt active power filter to regulate load terminal voltage, eliminate harmonics, and improve the power factor in systems with an uncontrolled rectifier and an AC controller as the non-linear loads. Different methods are used to control the active power filters. The reference current to be detected from the load current and processed by the active power filter controller is obtained from two different control algorithms, namely the Instantaneous Reactive Power Theory (PQ Theory) and Synchronous Reference Frame Theory (SRF Theory). The system is modeled and simulated using MATLAB/Simulink simulation package with a shunt active power filter to compensate for the harmonics current injected by the loads. It is then interfaced and verified using a Real-Time Digital Signal Processor DS1104 accompanied by an application (dSPACE) that is employed to view the simulation results and control the parameters of the simulation. 2009 IEEE.